Bioenergetics Consequences of Mitochondrial Transplantation in Cardiomyocytes. Issue 7 (9th April 2020) - Ali Pour, Paria; Kenney, M. Cristina; Kheradvar, Arash
Abstract : Background: Mitochondrial transplantation has been recently explored for treatment of very ill cardiac patients. However, little is known about the intracellular consequences of mitochondrial transplantation. This study aims to assess the bioenergetics consequences of mitochondrial transplantation into normal cardiomyocytes in the short and long term. Methods and Results: We first established the feasibility of autologous, non‐autologous, and interspecies mitochondrial transplantation. Then we quantitated the bioenergetics consequences of non‐autologous mitochondrial transplantation into cardiomyocytes up to 28 days using a Seahorse Extracellular Flux Analyzer. Compared with the control, we observed a statistically significant improvement in basal respiration and ATP production 2‐day post‐transplantation, accompanied by an increase in maximal respiration and spare respiratory capacity, although not statistically significantly. However, these initial improvements were short‐lived and the bioenergetics advantages return to the baseline level in subsequent time points. Conclusions: This study, for the first time, shows that transplantation of non‐autologous mitochondria from healthy skeletal muscle cells into normal cardiomyocytes leads to short‐term improvement of bioenergetics indicating "supercharged" state. However, over time these improved effects disappear, which suggests transplantation of mitochondria may have a potential application in settings where there is an acute stress.